Comunicação para o desenvolvimento: apoio a projetos de ajuda humanitária em sociedades pós-conflito e em conflito latente - o caso em Angola - Pugnaloni, Clara Maria (2011)
The study here presented follows the qualitative social research patterns in order to know the adoption of Communication for Development in two distinct moments for the realization of Humanitarian Help projects. In their initial phase, the Emergency one, when the first actions for the reorganization of the country are held by the International Organizations. And, in the Development phase, when the political and socioeconomic order and the fundamental rights become a priority. The objective was to get to know the actions for communication adopted by the International Organization (IO) and by selected the Non-Governmental Organizations (NGOs), in the Humanitarian Help projects which they develop. The aim of the thesis was to point the main actions for communications that might facilitate the implementation of the projects and the obtaining of the desired results. And, in this way, to collaborate with the rights holders, so that they are transformed in social actors, the way it is taught by the praxis of Paulo Freire pedagogy. As a final contribution, I developed a theoretical-operational reference in Communication for Development, possible to be adopted in future projects